Mesoplophoroidea (Acari, Oribatida) of China - Liu, Dong (Zootaxa, 2016)
The oribatid mite superfamily Mesoplophoroidea (Acari, Oribatida) is reviewed. Seven species in four genera of Mesoplophoroidea from China, including a new species, Mesoplophora (Mesoplophora) heterotricha sp. nov. from Hainan Province, are identified. Tritonymph of Apoplophora pantotrema (Berlese, 1913) is described based on material from China. A comprehensive, fully referenced checklist of all known species and keys to all known species worldwide are provided to facilitate the further study on this group.